PROJECT BASED LEARNING IMPLEMENTATION TRAINING FOR TEACHERS OF SMPN 44 SURABAYA - Anggun Purnomo Arbi (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
Project-based learning is one of the learning methods that has 21st century competencies and a scientific approach. Thus, project-based method training activities need to be carried out as an effort to improve the ability of educators. This community service was aimed to train SMPN 44 Surabaya teachers so that they are able to apply project-based learning in the process of implementing Curriculum Merdeka. This community service applied several methods called observation, discussion, and simulation. This activity was held on July 21, 2022, at SMPN 44 Surabaya. The participants of this community service were educators at SMPN 44 Surabaya. Based on the results and discussion, this training activity has been successfully implemented. This can be shown from the enthusiasm of the educators in the training process. Based on the results of discussions and simulations, the educators have succeeded in making sample projects and teaching modules. Therefore, this training activity is followed up with the provision of periodic evaluation activities.